Socio-demographic and health facility factors influencing utilization of reproductive health services among adolescents aged 15-19 years in Mombasa County, Kenya - Githogori, Nancy W.; Gitahi, Mary W.; Yonge, Shadrack A.; Bakari, Bibi A. (International Journal Of Community Medicine And Public Health, 2024)
Background: Globally, around 16 million teenagers give birth each year, with 95% of them coming from developing nations like Kenya, adolescents deal with a variety of sexual and reproductive health issues. Adolescent in Kenya frequently experiences serious health issues like unintended pregnancy, unsafe abortions, and sexually transmitted infections. Methods: A cross-sectional quantitative survey was conducted in Mombasa between August 2022-March, 2023. A validated questionnaire was used to collect data. Data collected were analysed using chi-square, Pearson’s correlation and multivariate linear regression tests. A total of 398 participants completed the survey questionnaire. A p<0.05 was statistically significant. Results: Major services utilized by respondents HIV testing and counseling 103 (13.2%) and condom use 61 (21.3%). Most reasons given by respondents for not seeking SRHS in health facilities were lack of need for the services (63.1%), no knowledge of where to go (43.20%), the lack of awareness of the availability of the services (27.90%), Stigma (22.50%). Factors that influence health facility utilization were provision of privacy/ confidentiality and provision of enabling environment to ask question which was statistically significant at (x2 =3.963, df=1, p=0.047) and (x2=5.695, df=1, p=0.017) respectively. Regarding socio-demographic variables, religion, education level and income were statistically significant (p<0.05). Conclusion: These findings underscore the importance of tailored interventions and targeted approaches to address the multifaceted factors influencing SRH service utilization among adolescents. Policymakers and healthcare practitioners can develop comprehensive strategies to promote access and utilization of SRH services among adolescents.